Does one size fit all? New service development across different types of services. (18th April 2017) - Jaakkola, Elina; Meiren, Thomas; Witell, Lars; Edvardsson, Bo; Schäfer, Adrienne; Reynoso, Javier; Sebastiani, Roberta; Weitlaner, Doris
Abstract : Purpose: The extant new service development (NSD) literature tends to assume that the key practices for NSD identified in one context apply for all services, and has failed to sufficiently consider differences in NSD between service types. The purpose of this paper is to explore the nature of NSD across different service types. Design/methodology/approach: An extensive, cross-sectoral survey was conducted in seven countries. Data from 1, 333 NSD projects were analyzed to empirically derive a service typology and examine if and how different types of services vary in terms of NSD resources, practices, methods, and results. Findings: Based on six service characteristics, the study identifies four service types: routine-intensive, technology-intensive, contact-intensive, and knowledge-intensive services. The study also identifies specific NSD resources, practices, methods, and results that are prevalent across the service typology. The evidence indicates that the use of advanced practices and methods differs dramatically between service types. Practical implications: The paper enables practitioners to expand their current understanding on NSD by providing insights into the variability of NSD across service types. The results suggest that either service-type-specific models or a configurable model for NSD should be developed. Originality/value: This study provides one of the first empirically derived service typologies for NSD. The study demonstrates that NSD resources, practices, methods, and results differ across service types, thereby challenging the "one size fits all" assumption evident in current NSD research.